Circular economy performance and carbon footprint of wind turbine blade waste management alternatives. (1st June 2023) - Diez-Cañamero, Borja; Mendoza, Joan Manuel F.
Highlights: Calculation of product circularity and global warming indicators. Evaluation of end-of-life management solutions to slow and close resource loops. Chemical recycling has the greater circularity and low-impact potential. Thermal recycling has the lower circularity and higher carbon footprint. Higher circularity does not always lead to carbon savings. Abstract: It is estimated that 570 Mt of blade waste, whose management is complex and expensive, will be generated by 2030 in the European Union alone. Accordingly, alternative blade waste management techniques are being investigated to optimize material recovery. This study evaluates the correlation between the circular economy performance and the carbon footprint of seven end-of-life management solutions for wind turbine blades: repurposing, grinding, solvolysis, pyrolysis, co-processing in cement kilns, incineration with energy recovery and landfilling. The circular economy performance is analyzed through the calculation of the product circularity indicator, while the carbon footprint is determined through life cycle assessment, using the global warming indicator and considering the management of three blades from cradle-to-gate as functional unit. As the performance of solvolysis and pyrolysis recycling is expected to change in the future, a sensitivity analysis is also carried out to evaluate the variability of the results by changing their process efficiency and the quality of the recovered materials. The results indicate that blade recycling through solvolysis is the most circular (0.47–0.77) and low-carbon (225–503 CO2 eq.) solution overall. Blade repurposing, grinding and cement co-processing have a similar circularity (0.52–0.55) and a global warming impact ranging from 499 t CO2 eq. to 615 t CO2 eq. Although the circularity of pyrolysis is 59% (0.35) to 118% (0.48) greater than the circularity of incineration and landfilling (0.22), its carbon footprint can range from 566 t CO2 eq. to 744 t CO2 eq, which could be up to 19% higher than the carbon footprint of these linear EoL management alternatives (623 t CO2 ). Based on these findings, proposals for sustainable industrial innovation and methodological recommendations for the development of integrated circularity and sustainability studies are proposed.